Mitochondrial haplotypes reveal a strong genetic structure for three Indian sheep breeds - Pardeshi, V. C.; Kadoo, Narendra Y.; Sainani, Mohini N.; Meadows, J. R. S.; Kijas, J. W.; Gupta, Vidya S. (Animal Genetics, 2007)
This survey represents the first characterization of mitochondrial DNA diversity within three breeds of Indian sheep (two strains of the Deccani breed, as well as the Bannur and Garole breeds) from different geographic regions and with divergent phenotypic characteristics. A 1061-bp fragment of the mitochondrial genome spanning the control region, a portion of the 12S rRNA gene and the complete phenyl tRNA gene, was sequenced from 73 animals and compared with the corresponding published sequence from European and Asian breeds and the European Mouflon (Ovis musimon). Analysis of all 156 sequences revealed 73 haplotypes, 52 of which belonged to the Indian breeds. The three Indian breeds had no haplotypes in common, but one Indian haplotype was shared with European and other Asian breeds. The highest nucleotide and haplotype diversity was observed in the Bannur breed (0.00355 and 0.981 respectively), while the minimum was in the Sangamneri strain of the Deccani breed (0.00167 and 0.882 respectively). All 52 Indian haplotypes belonged to mitochondrial lineage A. Therefore, these Indian sheep are distinct from other Asian and European breeds studied so far. The relationships among the haplotypes showed strong breed structure and almost no introgression among these Indian breeds, consistent with Indian sheep husbandry, which discourages genetic exchange between breeds. These results have implications for the conservation of India's ovine biodiversity and suggest a common origin for the breeds investigated.
Keywords: Genetic diversity; Indian sheep; mitochondrial DNA; mitochondrial lineage; phylogeographic distribution; sheep domestication

Molecular mapping of wilt resistance genes in chickpea - Gowda, S. J. M.; Radhika, P.; Kadoo, Narendra Y.; Mhase, L. B.; Gupta, V. S. (Molecular Breeding, 2009)
Fusarium wilt is a widespread and serious chickpea disease caused by the soil-borne fungus Fusarium oxysporum f.sp. ciceri (Foc). We evaluated an F(9) recombinant inbred line population of chickpea for resistance to three Foc races (1, 2 and 3) in pot culture experiments and identified flanking and tightly linked DNA markers for the resistance genes. The simple sequence repeat markers H3A12 and TA110 flanked the Foc1 locus at 3.9 and 2.1 cM, respectively, while Foc2 was mapped 0.2 cM from TA96 and 2.7 cM from H3A12. The H1B06y and TA194 markers flanked the Foc3 locus at 0.2 and 0.7 cM, respectively. These markers were also validated using 16 diverse chickpea genotypes. Identification of tightly linked flanking markers for wilt resistance genes will be useful for their exploitation in breeding programs and to understand the mechanism of resistance and evolution of the genes.
Keywords: fusarium oxysporum; Fusarium wilt; Genetic mapping; Marker validation; Pathogen races

QTL mapping of 1000-kernel weight, kernel length, and kernel width in bread wheat (Triticum aestivum L.) - Ramya, P.; Chaubal, A.; Kulkarni, K.; Gupta, L.; Kadoo, Narendra Y.; Dhaliwal, Harcharan Singh; Chhuneja, Parveen; Lagu, Meena D.; Gupta, V. (Journal of Applied Genetics, 2010)
Kernel size and morphology influence the market value and milling yield of bread wheat (Triticum aestivum L.). The objective of this study was to identify quantitative trait loci (QTLs) controlling kernel traits in hexaploid wheat. We recorded 1000-kernel weight, kernel length, and kernel width for 185 recombinant inbred lines from the cross Rye Selection 111 x Chinese Spring grown in 2 agro-climatic regions in India for many years. Composite interval mapping (CIM) was employed for QTL detection using a linkage map with 169 simple sequence repeat (SSR) markers. For 1000-kernel weight, 10 QTLs were identified on wheat chromosomes 1A, 1D, 2B, 2D, 4B, 5B, and 6B, whereas 6 QTLs for kernel length were detected on 1A, 2B, 2D, 5A, 5B and 5D. Chromosomes 1D, 2B, 2D, 4B, 53 and 5D had 9 QTLs for kernel width. Chromosomal regions with QTLs detected consistently for multiple year-location combinations were identified for each trait. Pleiotropic QTLs were found on chromosomes 2B, 2D, 4B, and 5B. The identified genomic regions controlling wheat kernel size and shape can be targeted during further studies for their genetic dissection.
Keywords: composite interval mapping; kernel shape; kernel size; quantitative trait loci; Stable QTLs; Triticum aestivum

Relatedness of Indian flax genotypes (Linum usitatissimum L.): an inter-simple sequence repeat (ISSR) primer assay - Rajwade, Ashwini V.; Arora, Ritu S.; Kadoo, Narendra Y.; Harsulkar, Abhay M.; Ghorpade, Prakash B.; Gupta, Vidya S. (Molecular Biotechnology, 2010)
The objective of this study was to analyze the genetic relationships, using PCR-based ISSR markers, among 70 Indian flax (Linum usitatissimum L.) genotypes actively utilized in flax breeding programs. Twelve ISSR primers were used for the analysis yielding 136 loci, of which 87 were polymorphic. The average number of amplified loci and the average number of polymorphic loci per primer were 11.3 and 7.25, respectively, while the percent loci polymorphism ranged from 11.1 to 81.8 with an average of 63.9 across all the genotypes. The range of polymorphism information content scores was 0.03-0.49, with an average of 0.18. A dendrogram was generated based on the similarity matrix by the Unweighted Pair Group Method with Arithmetic Mean (UPGMA), wherein the flax genotypes were grouped in five clusters. The Jaccard's similarity coefficient among the genotypes ranged from 0.60 to 0.97. When the omega-3 alpha linolenic acid (ALA) contents of the individual genotypes were correlated with the clusters in the dendrogram, the high ALA containing genotypes were grouped in two clusters. This study identified SLS 50, Ayogi, and Sheetal to be the most diverse genotypes and suggested their use in breeding programs and for developing mapping populations.
Keywords: ALA; Alpha linolenic acid; Diversity assessment; Linseed; Oil content; Omega-3 fatty acid

Understanding the genetic structure of symplocos laurina wall. populations using nuclear gene markers - Banu, Sofia; Bhagwat, Rasika M.; Kadoo, Narendra Y.; Lagu, Meena D.; Gupta, V. S. (Genetica, 2010)
To characterize the genetic diversity of present populations of Symplocos laurina, which grow in the montane forests in India, we analyzed the DNA sequences of a nuclear gene. Using the 881 bp sequence of cytosolic Glyceraldehyde-3-phosphate dehydrogenase gene, we detected 24 haplotypes among 195 individuals sampled from 14 populations. Two dominant haplotypes were distributed over the entire range of this species in India and several private haplotypes were found. Low genetic diversity within population, high differentiation, number of population specific haplotypes and deviation from neutral evolution characterized the present populations of S. laurina. An analysis of molecular variance indicated the presence of geographic structure within the haplotype distribution. The occurrence of S. laurina preglaciation in India is the most parsimonious explanation for the current geographic structure observed. The populations are presumably ancient and might have spread across its extant distribution range in India through a recent range expansion event.
Keywords: GapC; Genetic diversity; Glaciation; Refugium

Auxin signaling and transport promote susceptibility to the root-infecting fungal pathogen fusarium oxysporum in arabidopsis - Kidd, Brendan N.; Kadoo, Narendra Y.; Dombrecht, Bruno; Tekeoglu, Muecella; Gardiner, Donald M.; Thatcher, Louise F.; Aitken, Elizabeth A. B.; Schenk, Peer M.; Manners, John M.; Kazan, Kemal (Molecular Plant-Microbe Interactions, 2011)

Mapping of QTLs governing agronomic and yield traits in chickpea - Gowda, S. J. M.; Radhika, P.; Mhase, L. B.; Jamadagni, B. M.; Gupta, V. S.; Kadoo, Narendra Y. (Journal of Applied Genetics, 2011)
Chickpea is one of the most important leguminous cool season food crops, cultivated prevalently in South Asia and Middle East. The main objective of this study was to identify quantitative trait loci (QTLs) associated with seven agronomic and yield traits in two recombinant inbred line populations of chickpea derived from the crosses JG62xVijay (JV population) and VijayxICC4958 (VI population) from at least three environments. Single locus QTL analysis involved composite interval mapping (CIM) for individual traits and multiple-trait composite interval mapping (MCIM) for correlated traits to detect pleiotropic QTLs. Two-locus analysis was conducted to identify the main effect QTLs (M-QTLs), epistatic QTLs (E-QTLs) and QTL x environment interactions. Through CIM analysis, a total of 106 significant QTLs (41 in JV and 65 in VI populations) were identified for the seven traits, of which one QTL each for plant height and days to maturity was common in both the populations. Six pleiotropic QTLs that were consistent over the environments were also identified. LG2 in JV and LG1a in VI contained at least one QTL for each trait. Hence, concentrating on these LGs in molecular breeding programs is most likely to bring simultaneous improvement in these traits.
Keywords: Cicer arietinum; QTL analysis; QTL x environment interaction; Two-locus analysis; Yield traits

Development of genomic simple sequence repeat markers for linseed using next-generation sequencing technology - Kale, Sandip M.; Pardeshi, Varsha C.; Kadoo, Narendra Y.; Ghorpade, Prakash B.; Jana, Murari M.; Gupta, Vidya S. (Molecular Breeding, 2012)
Linseed (Linum usitatissimum L.) is regarded as a cash crop of tomorrow because of the presence of nutraceutically important alpha-linolenic acid (ALA) and lignan. However, only limited breeding progress has been made in this crop, mainly due to the lack of sufficient genetic and genomic resources. Among these, simple sequence repeats (SSR) are useful DNA markers for diversity analysis, genetic mapping and tagging traits because of their co-dominant and highly polymorphic nature. In order to develop SSR markers for linseed, we used three microsatellite isolation methods, viz., PCR Isolation of Microsatellite Arrays (PIMA), 5'-anchored PCR method, and Fast Isolation by AFLP of Sequences COntaining repeats (FIASCO). The amplified products from these methods were pooled and sequenced using the 454 GS-FLX platform. A total of 36,332 reads were obtained, which assembled into 2,183 contigs and 2,509 singlets. The contigs and the singlets contained 1,842 microsatellite motifs, with dinucleotide motifs as the most abundant repeat type (54%) followed by trinucleotide motifs (44%). Based on this, 290 SSR markers were designed, 52 of which were evaluated using a panel of 27 diverse linseed genotypes. Among the three enrichment methods, the 5'-anchored PCR method was most efficient for isolation of microsatellites, while FIASCO was most efficient for developing SSR markers. We show the utility of next-generation sequencing technology for efficiently discovering a large number of microsatellite markers in non-model plants.
Keywords: Flax; Microsatellite isolation; Next-generation sequencing; SSR

Kernel morphometric traits in hexaploid wheat (Triticum aestivum L.) are modulated by intricate QTL x QTL and genotype x environment interactions - Prashant, Ramya; Kadoo, Narendra Y.; Desale, Charushila; Kore, Prajakta; Dhaliwal, Harcharan Singh; Chhuneja, Parveen; Gupta, Vidya (Journal of Cereal Science, 2012)
Wheat kernel size and shape influence its flour yield and market price. A hexaploid wheat population of 185 recombinant inbred lines was evaluated for five kernel morphometric traits namely, 1000-kernel weight, kernel length, width, length width ratio and factor form density in two diverse agro-climatic regions in India in five to eight year location combinations. Additive main effects and multiplicative interaction analysis revealed significant contributions from genotype (G) and genotype x environment (G x E) effects for these traits. Quantitative trait locus (QTL) analysis by composite interval mapping (CIM) was performed using a linkage map of 251 SSR markers and 59 QTLs distributed on 16 chromosomes were identified. The majority of the QTLs were located on the D genome (44.07%) and the homeologous chromosomes of Group 2 (38.98%). Stable QTLs detected in three or more year location combinations were identified for four traits. Multi-trait CIM showed 10 chromosomal regions harboring putative pleiotropic loci. Complexity in the genetic effects was further revealed by QTL analysis based on mixed-linear model that indicated 19 QTLs with significant individual effects (main-effect QTLs) and 14 QTL x QTL interactions. Five of these - nineteen main-effect QTLs and one of the fourteen QTL x QTL interactions showed environmental influence. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Epistatic QTLs; Genotype x environment interactions; Kernel size and shape; Stable QTLs

Phylogenomic analysis of UDP glycosyltransferase 1 multigene family in Linum usitatissimum identified genes with varied expression patterns - Barvkar, Vitthal T.; Pardeshi, Varsha C.; Kale, Sandip M.; Kadoo, Narendra Y.; Gupta, Vidya S. (BMC Genomics, 2012)
Background: The glycosylation process, catalyzed by ubiquitous glycosyltransferase (GT) family enzymes, is a prevalent modification of plant secondary metabolites that regulates various functions such as hormone homeostasis, detoxification of xenobiotics and biosynthesis and storage of secondary metabolites. Flax (Linum usitatissimum L.) is a commercially grown oilseed crop, important because of its essential fatty acids and health promoting lignans. Identification and characterization of UDP glycosyltransferase (UGT) genes from flax could provide valuable basic information about this important gene family and help to explain the seed specific glycosylated metabolite accumulation and other processes in plants. Plant genome sequencing projects are useful to discover complexity within this gene family and also pave way for the development of functional genomics approaches. Results: Taking advantage of the newly assembled draft genome sequence of flax, we identified 137 UDP glycosyltransferase (UGT) genes from flax using a conserved signature motif. Phylogenetic analysis of these protein sequences clustered them into 14 major groups (A-N). Expression patterns of these genes were investigated using publicly available expressed sequence tag (EST), microarray data and reverse transcription quantitative real time PCR (RT-qPCR). Seventy-three per cent of these genes (100 out of 137) showed expression evidence in 15 tissues examined and indicated varied expression profiles. The RT-qPCR results of 10 selected genes were also coherent with the digital expression analysis. Interestingly, five duplicated UGT genes were identified, which showed differential expression in various tissues. Of the seven intron loss/gain positions detected, two intron positions were conserved among most of the UGTs, although a clear relationship about the evolution of these genes could not be established. Comparison of the flax UGTs with orthologs from four other sequenced dicot genomes indicated that seven UGTs were flax diverged. Conclusions: Flax has a large number of UGT genes including few flax diverged ones. Phylogenetic analysis and expression profiles of these genes identified tissue and condition specific repertoire of UGT genes from this crop. This study would facilitate precise selection of candidate genes and their further characterization of substrate specificities and in planta functions.

Proteome profiling of flax (linum usitatissimum) seed: characterization of functional metabolic pathways operating during seed development - Barvkar, Vitthal T.; Pardeshi, Varsha C.; Kale, Sandip M.; Kadoo, Narendra Y.; Giri, Ashok P.; Gupta, Vidya S. (Journal of Proteome Research, 2012)
Flax (Linum usitatissimum L.) seeds are an important source of food and feed due to the presence of various health promoting compounds, making it a nutritionally and economically important plant. An in-depth analysis of the proteome of developing flax seed is expected to provide significant information with respect to the regulation and accumulation of such storage compounds. Therefore, a proteomic analysis of seven seed developmental stages (4, 8, 12, 16, 22, 30, and 48 days after anthesis) in a flax variety, NL-97 was carried out using a combination of ID-SDS-PAGE and LC-MSE methods. A total 1716 proteins were identified and their functional annotation revealed that a majority of them were involved in primary metabolism, protein destination, storage and energy. Three carbon assimilatory pathways appeared to operate in flax seeds. Reverse transcription quantitative PCR of selected 19 genes was carried out to understand their roles during seed development. Besides storage proteins, methionine synthase, RuBisCO and S-adenosylmethionine synthetase were highly expressed transcripts, highlighting their importance in flax seed development. Further, the identified proteins were mapped onto developmental seed specific expressed sequence tag (EST) libraries of flax to obtain transcriptional evidence and 81% of them had detectable expression at the mRNA level. This study provides new insights into the complex seed developmental processes operating in flax.
Keywords: alpha-linolenic acid; carbon flux; Digital expression analysis; flax seed development; MSE; secoisolariciresinol diglucoside

Genome-wide identification and characterization of microRNA genes and their targets in flax (Linum usitatissimum) - Barvkar, Vitthal T.; Pardeshi, Varsha C.; Kale, Sandip M.; Qiu, Shuqing; Rollins, Meaghen; Datla, Raju; Gupta, Vidya S.; Kadoo, Narendra Y. (Planta, 2013)
MicroRNAs (miRNAs) are small (20-24 nucleotide long) endogenous regulatory RNAs that play important roles in plant growth and development. They regulate gene expression at the post-transcriptional level by translational repression or target degradation and gene silencing. In this study, we identified 116 conserved miRNAs belonging to 23 families from the flax (Linum usitatissimum L.) genome using a computational approach. The precursor miRNAs varied in length; while most of the mature miRNAs were 21 nucleotide long, intergenic and showed conserved signatures of RNA polymerase II transcripts in their upstream regions. Promoter region analysis of the flax miRNA genes indicated prevalence of MYB transcription factor binding sites. Four miRNA gene clusters containing members of three phylogenetic groups were identified. Further, 142 target genes were predicted for these miRNAs and most of these represent transcriptional regulators. The miRNA encoding genes were expressed in diverse tissues as determined by digital expression analysis as well as real-time PCR. The expression of fourteen miRNAs and nine target genes was independently validated using the quantitative reverse transcription PCR (qRT-PCR). This study suggests that a large number of conserved plant miRNAs are also found in flax and these may play important roles in growth and development of flax.
Keywords: Digital expression analysis; Gene cluster; Linseed; miRNA; MiRNA target transcript; Promoter analysis

Genome-wide identification and characterization of nucleotide binding site leucine-rich repeat genes in linseed reveal distinct patterns of gene structure - Kale, Sandip M.; Pardeshi, Varsha C.; Barvkar, Vitthal T.; Gupta, Vidya S.; Kadoo, Narendra Y. (Genome, 2013)
Plants employ different disease-resistance genes to detect pathogens and to induce defense responses. The largest class of these genes encodes proteins with nucleotide binding site (NBS) and leucine-rich repeat (LRR) domains. To identify the putative NBS-LRR encoding genes from linseed, we analyzed the recently published linseed genome sequence and identified 147 NBS-LRR genes. The NBS domain was used for phylogeny construction and these genes were classified into two well-known families, non-TIR (CNL) and TIR related (TNL), and formed eight clades in the neighbor-joining bootstrap tree. Eight different gene structures were observed among these genes. An unusual domain arrangement was observed in the TNL family members, predominantly in the TNL-5 clade members belonging to class D. About 12% of the genes observed were linseed specific. The study indicated that the linseed genes probably have an ancient origin with few progenitor genes. Quantitative expression analysis of five genes showed inducible expression. The in silico expression evidence was obtained for a few of these genes, and the expression was not correlated with the presence of any particular regulatory element or with unusual domain arrangement in those genes. This study will help in understanding the evolution of these genes, the development of disease resistant varieties, and the mechanism of disease resistance in linseed.
Keywords: Flax; in silico gene expression; motif analysis; NBS-LRR; Phylogenetic analysis; Promoter analysis

Differential transcriptional activity of SAD, FAD2 and FAD3 desaturase genes in developing seeds of linseed contributes to varietal variation in alpha-linolenic acid content - Rajwade, Ashwini V.; Kadoo, Narendra Y.; Borikar, Sanjay P.; Harsulkar, Abhay M.; Ghorpade, Prakash B.; Gupta, Vidya S. (Phytochemistry, 2014)
Linseed or flax (Linum usitatissimum L.) varieties differ markedly in their seed a-linolenic acid (ALA) levels. Fatty acid desaturases play a key role in accumulating ALA in seed. We performed fatty acid (FA) profiling of various seed developmental stages of ten Indian linseed varieties including one mutant variety. Depending on their ALA contents, these varieties were grouped under high ALA and low ALA groups. Transcript profiling of six microsomal desaturase genes (SAD1, SAD2, FAD2, FAD2-2, FAD3A and FAD3B), which act sequentially in the fatty acid desaturation pathway, was performed using real-time PCR. We observed gene specific as well as temporal expression pattern for all the desaturases and their differential expression profiles corresponded well with the variation in FA accumulation in the two groups. Our study points to efficient conversion of intermediate FAs [stearic (SA), oleic (OA) and linoleic acids (LA)] to the final product, ALA, due to efficient action of all the desaturases in high ALA group. While in the low ALA group, even though the initial conversion up to OA was efficient, later conversions up to ALA seemed to be inefficient, leading to higher accumulation of OA and LA instead of ALA. We sequenced the six desaturase genes from the ten varieties and observed that variation in the amino acid (AA) sequences of desaturases was not responsible for differential ALA accumulation, except in the mutant variety TL23 with very low (<2%) ALA content. In TL23, a point mutation in the FAD3A gene resulted into a premature stop codon generating a truncated protein with 291 AA. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: ALA; Fatty acid desaturases; Fatty acids; Flax; Gene expression; Linseed

Evaluation of genetic variability in Symplocos laurina Wall. from two biodiversity hotspots of India - Bhagwat, Rasika M.; Banu, Sofia; Dholakia, Bhushan B.; Kadoo, Narendra Y.; Lagu, Meena D.; Gupta, Vidya S. (Plant Systematics and Evolution, 2014)
Symplocos laurina Wall., an important medicinal tree species, is one of the pioneering plants for establishment of shola forest ecosystem. We analyzed 208 accessions of S. laurina from 13 populations belonging to three ecoregions in India namely, Western Ghats, Eastern Ghats and Northeast India, to comment on the genetic diversity and population structure of the species. Of the 100 inter simple sequence repeat primers screened, eight were selected based on their clear and reproducible polymorphic patterns. These eight ISSR primers produced on an average 1,014 bands from 208 accessions, of which 6.58 % were rare bands, 55.96 % were shared bands and 37.46 % were similar bands. The primers, UBC835 and UBC880, amplified the highest number of polymorphic loci (16), while the primer UBC852 amplified the least number of amplicons (9). The values for total genetic diversity (H-T) and the average heterozygosity (H-S) were 0.3407 and 0.2263, respectively; while the coefficient of genetic differentiation (G(ST)) was 0.3358. Within-population variance was higher (68 %) than among-population variance (17 %), indicating high intra-population genetic diversity. These populations were grouped according to their geographical location in cluster analysis. Mantel test also showed significant positive correlation between genetic and geographical distances. The present study revealed the importance of the Palghat gap in South India in shaping the distribution of genetic diversity in S. laurina.
Keywords: Biodiversity hotspots; Genetic diversity; ISSR; Palghat gap; Symplocos laurina

Analysis of genetic variability in Aquilaria malaccensis from Bramhaputra valley, Assam, India using ISSR markers - Banu, Sofia; Baruah, Darshana; Bhagwat, Rasika M.; Sarkar, Purabi; Bhowmick, Ananya; Kadoo, Narendra Y. (Flora, 2015)

Expression of stable reference genes and SPINDLY gene in response to gibberellic acid application at different stages of grapevine development - Upadhyay, A.; Jogaiah, S.; Maske, S. R.; Kadoo, Narendra Y.; Gupta, V. S. (Biologia Plantarum, 2015)
Gibberellic acid (GA(3)) is widely used at different stages of berry development, and to understand the molecular mechanism of its action requires identification of stable reference genes. We sprayed grapevine (Vitis vinifera L.) cv. Thompson Seedless with GA(3) at rachis stage for rachis elongation, at flower cluster stage for flower thinning, and at 3 - 4 mm berry stage for berry elongation. Tissue samples were collected at different time points after GA(3) application. The expression of 10 candidate reference genes was analyzed using 4 different algorithms to assess their suitability for real time-PCR data normalization. Based on the overall ranking, PP2A, Sutra, and SAND were identified as the most stably expressed genes across all samples. With regard to different stages, tubulin, EF1 alpha, and UBC were the most stable genes during rachis elongation; PP2A, SAND, and Sutra were the most suitable at the flower cluster and berry stages. The expression of GA signaling gene SPINDLY (VvSpy) was analyzed to validate the stable reference genes. After the GA(3) application, the expression of VvSpy was reduced at the rachis stage but did not change at the flower cluster and berry stages. The expression profile of VvSpy was comparable when two or three reference genes were used for data normalization.
Keywords: developmental stages; Vitis vinifera

Genotype x environment interactions and QTL clusters underlying dough rheology traits in triticum aestivum L. - Prashant, Ramya; Mani, Elangovan; Rai, Richa; Gupta, R. K.; Tiwari, Ratan; Dholakia, Bhushan B.; Oak, Manoj; Roeder, Marion; Kadoo, Narendra Y.; Gupta, Vidya (Journal of Cereal Science, 2015)
Genetic dissection of dough rheology traits (DRT) in hexaploid wheat was carried out using nine mixograph characters evaluated in two consecutive years in three agro-climatic zones in India in an RIL population (HI977 x HD2329). Pearson correlations determined in each year-location indicated 15 stable trait inter-relationships among them but inconsistent correlations with loaf volume (LV) were observed. Using AMMI analysis we derived patterns in G x E interactions (GEI) indicating 6-47% contribution for the DRT. Composite interval mapping using a linkage map of 202 SSR markers identified 144 DRT QTLs of which, 96 were detected in single- and the rest in two to five year-locations. Sixteen QTL clusters located on ten chromosomes were identified and only three of them on chromosomes 1B, 5B and 6D involved LV QTLs. For each trait, majority of the DRT QTLs detected in single as well as multiple environments showed location-specificity and suggested that owing to GEI, breeding for wheat dough quality might need careful selection of QTLs targeted for individual agro-climatic zones. The inconsistent correlations of DRT and LV and differential locations of their QTLs in this population corroborated that using dough rheological traits alone to predict LV might pose challenges during wheat improvement. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: AMMI analysis; Dough rheology; Mixograph; QTL

Metabolic profiling of chickpea-Fusarium interaction identifies differential modulation of disease resistance pathways - Kumar, Yashwant; Dholakia, Bhushan B.; Panigrahi, Priyabrata; Kadoo, Narendra Y.; Giri, Ashok P.; Gupta, Vidya S. (Phytochemistry, 2015)
Chickpea is the third most widely grown legume in the world and mainly used as a vegetarian source of human dietary protein. Fusarium wilt, caused by Fusarium oxysporum f. sp. ciceri (Foc), is one of the major threats to global chickpea production. Host resistance is the best way to protect crops from diseases; however, in spite of using various approaches, the mechanism of Foc resistance in chickpea remains largely obscure. In the present study, non-targeted metabolic profiling at several time points of resistant and susceptible chickpea cultivars using high-resolution liquid chromatography-mass spectrometry was applied to better understand the mechanistic basis of wilt resistance or susceptibility. Multivariate analysis of the data (OPLS-DA) revealed discriminating metabolites in chickpea root tissue after Foc inoculation such as flavonoids, isoflavonoids, alkaloids, amino acids and sugars. Foc inoculated resistant plants had more flavonoids and isoflavonoids along with their malonyl conjugates. Many antifungal metabolites that were induced after Foc infection viz, aurantion-obstine beta-glucosides and querecitin were elevated in resistant cultivar. Overall, diverse genetic and biochemical mechanisms were operational in the resistant cultivar for Foc defense as compared to the susceptible plant. The resistant chickpea plants employed the above-mentioned metabolic pathways as potential defense strategy against Foc. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Chickpea; Fusarium wilt; LC-MS; Metabolomics; OPLS-DA; Phytoalexin

Two new potential barcodes to discriminate dalbergia species - Bhagwat, Rasika M.; Dholakia, Bhushan B.; Kadoo, Narendra Y.; Balasundaran, M.; Gupta, Vidya S. (Plos One, 2015)
DNA barcoding enables precise identification of species from analysis of unique DNA sequence of a target gene. The present study was undertaken to develop barcodes for different species of the genus Dalbergia, an economically important timber plant and is widely distributed in the tropics. Ten Dalbergia species selected from the Western Ghats of India were evaluated using three regions in the plastid genome (matK, rbcL, trnH-psbA), a nuclear transcribed spacer (nrITS) and their combinations, in order to discriminate them at species level. Five criteria: (i) inter and intraspecific distances, (ii) Neighbor Joining (NJ) trees, (iii) Best Match (BM) and Best Close Match (BCM), (iv) character based rank test and (v) Wilcoxon signed rank test were used for species discrimination. Among the evaluated loci, rbcL had the highest success rate for amplification and sequencing (97.6%), followed by matK (97.0%), trnH-psbA (94.7%) and nrITS (80.5%). The inter and intraspecific distances, along with Wilcoxon signed rank test, indicated a higher divergence for nrITS. The BM and BCM approaches revealed the highest rate of correct species identification (100%) with matK, matK+rbcL and matK+trnH-psb loci. These three loci, along with nrITS, were further supported by character based identification method. Considering the overall performance of these loci and their ranking with different approaches, we suggest matK and matK+rbcL as the most suitable barcodes to unambiguously differentiate Dalbergia species. These findings will potentially be helpful in delineating the various species of Dalbergia genus, as well as other related genera.

Biosynthesis of anti-proliferative gold using endophytic fusarium oxysporum strain isolated from neem (A-indica) leaves - Siddiqui, Ejaz Ahmad; Ahmad, Absar; Julius, Anju; Syed, Asad; Khan, Shadab; Kharat, Mahesh; Pai, Kalpana; Kadoo, Narendra Y.; Gupta, Vidya (Current topics in medicinal chemistry, 2016)
Here we report a simple, rapid, environment friendly approach for the synthesis of gold nanoparticles using neem (Azadirachta indica A. Juss.) fungal endophyte, which based upon morphological and cultural characteristics was eventually identified as Fusarium oxysporum. The aqueous precursor (HAuCl4) solution when reacted with endophytic fungus resulted in the biosynthesis of abundant amounts of well dispersed gold nanoparticles of 10-40 nm with an average size of 22nm. These biosynthesized gold nanoparticles were then characterized by standard analytical techniques such as UV-Visible spectroscopy, X-ray diffraction, Transmission Electron Microscopy and Fourier Transform Infrared Spectroscopy. Cytotoxic activity of these nanoparticles was checked against three different cell types including breast cancer (ZR-75-1), Daudi (Human Burkitt's lymphoma cancer) and normal human peripheral blood mononuclear cells (PBMC), where it was found that our gold nanoparticles are anti-proliferative against cancer cells but completely safe toward normal cells. In addition to this, assessment of toxicity toward human RBC revealed less than 0.1 % hemolysis as compared to Triton X-100 suggesting safe nature of our biosynthesized gold nanoparticles on human cells. Also, our nanoparticles exhibited no anti-fungal (against Aspergillus niger) or anti-bacterial [against Gram positive (Bacillus subtilis & Staphylococcus aureus) and Gram negative (Escherichia coli & Pseudomonas aeruginosa) bacteria] activity thus suggesting their non-toxic, biocompatible nature. The present investigation opens up avenues for eco-friendly, biocompatible nanomaterials to be used in a wide variety of application such as drug delivery, therapeutics, theranostics and so on.

Dynamics of colonization and expression of pathogenicity related genes in fusarium oxysporum f.sp ciceri during chickpea vascular wilt disease progression - Upasani, Medha L.; Gurjar, Gayatri S.; Kadoo, Narendra Y.; Gupta, Vidya S. (Plos One, 2016)
Fusarium wilt caused by Fusarium oxysporum f.sp. ciceri (Foc) is a constant threat to chickpea productivity in several parts of the world. Understanding the molecular basis of chickpea-Foc interaction is necessary to improve chickpea resistance to Foc and thereby the productivity of chickpea. We transformed Foc race 2 using green fluorescent protein (GFP) gene and used it to characterize pathogen progression and colonization in wilt-susceptible (JG62) and wilt-resistant (Digvijay) chickpea cultivars using confocal microscopy. We also employed quantitative PCR (qPCR) to estimate the pathogen load and progression across various tissues of both the chickpea cultivars during the course of the disease. Additionally, the expression of several candidate pathogen virulence genes was analyzed using quantitative reverse transcriptase PCR (qRT-PCR), which showed their characteristic expression in wilt-susceptible and resistant chickpea cultivars. Our results suggest that the pathogen colonizes the susceptible cultivar defeating its defense; however, albeit its entry in the resistant plant, further proliferation is severely restricted providing an evidence of efficient defense mechanism in the resistant chickpea cultivar.

Fusarium oxysporum mediates systems metabolic reprogramming of chickpea roots as revealed by a combination of proteomics and metabolomics - Kumar, Yashwant; Zhang, Limin; Panigrahi, Priyabrata; Dholakia, Bhushan B.; Dewangan, Veena; Chavan, Sachin G.; Kunjir, Shrikant M.; Wu, Xiangyu; Li, Ning; Rajmohanan, Pattuparambil R.; Kadoo, Narendra Y.; Giri, Ashok P.; et al. (Plant Biotechnology Journal, 2016)
Molecular changes elicited by plants in response to fungal attack and how this affects plant-pathogen interaction, including susceptibility or resistance, remain elusive. We studied the dynamics in root metabolism during compatible and incompatible interactions between chickpea and Fusarium oxysporum f. sp. ciceri (Foc), using quantitative label-free proteomics and NMR-based metabolomics. Results demonstrated differential expression of proteins and metabolites upon Foc inoculations in the resistant plants compared with the susceptible ones. Additionally, expression analysis of candidate genes supported the proteomic and metabolic variations in the chickpea roots upon Foc inoculation. In particular, we found that the resistant plants revealed significant increase in the carbon and nitrogen metabolism; generation of reactive oxygen species (ROS), lignification and phytoalexins. The levels of some of the pathogenesis-related proteins were significantly higher upon Foc inoculation in the resistant plant. Interestingly, results also exhibited the crucial role of altered Yang cycle, which contributed in different methylation reactions and unfolded protein response in the chickpea roots against Foc. Overall, the observed modulations in the metabolic flux as outcome of several orchestrated molecular events are determinant of plant's role in chickpea-Foc interactions.
Keywords: Chickpea; fusarium oxysporum; Metabolomics; NMR; plant-pathogen interaction; proteomics

Sequence characterization and in silico structure prediction of fatty acid desaturases in linseed varieties with differential fatty acid composition - Rajwade, Ashwini V.; Joshi, Rakesh S.; Kadoo, Narendra Y.; Gupta, Vidya S. (Journal of the Science of Food and Agriculture, 2016)
BACKGROUND: Linseed is the richest agricultural source of alpha-linolenic acid (ALA), an omega-3 fatty acid (FA) that offers several nutritional benefits. In the present study, sequence characterization of six desaturase genes (SAD1, SAD2, FAD2, FAD2-2, FAD3A and FAD3B) and 3D structure prediction of their proteins from ten Indian linseed varieties differing in ALA content were performed to determine whether the nucleotide and amino acid (AA) sequence variants have any functional implications in differential accumulation of ALA or other FAs in linseed. RESULTS: The SAD and FAD2 genes exhibited few sequence variations among the ten varieties, forming only one or two protein isoforms. In contrast, the FAD3A and FAD3B genes showed more sequence variations and three or four protein isoforms. Interestingly, the two high-ALA varieties NL260 and Padmini had the same FAD3B nucleotide and protein isoforms, which differed from all other varieties. Surprisingly, no AA changes altered the 3D structures of the desaturase proteins. CONCLUSION: Several nucleotide and AA sequence variations in desaturase genes were observed; however, they did not alter the 3D structure of any desaturase protein and were not correlated with FA levels among the ten linseed varieties, which had different ALA contents. This suggests a complex regulatory process of biosynthesis of FAs in linseed. (C) 2016 Society of Chemical Industry

Chickpea-fusarium oxysporum interaction transcriptome reveals differential modulation of plant defense strategies - Upasani, Medha L.; Limaye, Bhakti M.; Gurjar, Gayatri S.; Kasibhatla, Sunitha M.; Joshi, Rajendra R.; Kadoo, Narendra Y.; Gupta, Vidya S. (Scientific Reports, 2017)
Fusarium wilt is one of the major biotic stresses reducing chickpea productivity. The use of wilt-resistant cultivars is the most appropriate means to combat the disease and secure productivity. As a step towards understanding the molecular basis of wilt resistance in chickpea, we investigated the transcriptomes of wilt-susceptible and wilt-resistant cultivars under both Fusarium oxysporum f.sp. ciceri (Foc) challenged and unchallenged conditions. Transcriptome profiling using LongSAGE provided a valuable insight into the molecular interactions between chickpea and Foc, which revealed several known as well as novel genes with differential or unique expression patterns in chickpea contributing to lignification, hormonal homeostasis, plant defense signaling, ROS homeostasis, R-gene mediated defense, etc. Similarly, several Foc genes characteristically required for survival and growth of the pathogen were expressed only in the susceptible cultivar with null expression of most of these genes in the resistant cultivar. This study provides a rich resource for functional characterization of the genes involved in resistance mechanism and their use in breeding for sustainable wilt-resistance. Additionally, it provides pathogen targets facilitating the development of novel control strategies.

Transcriptional transitions in alphonso mango (Mangifera indica L.) during fruit development and ripening explain its distinct aroma and shelf life characteristics - Deshpande, Ashish B.; Anamika, Krishanpal; Jha, Vineet; Chidley, Hemangi G.; Oak, Pranjali S.; Kadoo, Narendra Y.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Scientific Reports, 2017)
Alphonso is known as the "King of mangos" due to its unique flavor, attractive color, low fiber pulp and long shelf life. We analyzed the transcriptome of Alphonso mango through Illumina sequencing from seven stages of fruit development and ripening as well as flower. Total transcriptome data from these stages ranged between 65 and 143 Mb. Importantly, 20,755 unique transcripts were annotated and 4,611 were assigned enzyme commission numbers, which encoded 142 biological pathways. These included ethylene and flavor related secondary metabolite biosynthesis pathways, as well as those involved in metabolism of starch, sucrose, amino acids and fatty acids. Differential regulation ( p-value <= 0.05) of thousands of transcripts was evident in various stages of fruit development and ripening. Novel transcripts for biosynthesis of mono-terpenes, sesqui-terpenes, di-terpenes, lactones and furanones involved in flavor formation were identified. Large number of transcripts encoding cell wall modifying enzymes was found to be steady in their expression, while few were differentially regulated through these stages. Novel 79 transcripts of inhibitors of cell wall modifying enzymes were simultaneously detected throughout Alphonso fruit development and ripening, suggesting controlled activity of these enzymes involved in fruit softening.

GA3 application in grapes (Vitis vinifera L.) modulates different sets of genes at cluster emergence, full bloom, and berry stage as revealed by RNA sequence-based transcriptome analysis - Upadhyay, Anuradha; Maske, Smita; Jogaiah, Satisha; Kadoo, Narendra Y.; Gupta, Vidya S. (Functional & Integrative Genomics, 2018)
In grapes (Vitis vinifera L.), exogenous gibberellic acid (GA3) is applied at different stages of bunch development to achieve desirable bunch shape and berry size in seedless grapes used for table purpose. RNA sequence-based transcriptome analysis was used to understand the mechanism of GA3 action at cluster emergence, full bloom, and berry stage in table grape variety Thompson Seedless. At cluster emergence, rachis samples were collected at 6 and 24 h after application of GA3, whereas flower clusters and berry samples were collected at 6, 24, and 48 h after application at full bloom and 3–4 mm berry stages. Seven hundred thirty-three genes were differentially expressed in GA3-treated samples. At rachis and flower cluster stage respectively, 126 and 264 genes were found to be significantly differentially expressed within 6 h of GA3 application. The number of DEG reduced considerably at 24 h. However, at berry stage, major changes occurred even at 24 h and a number of DEGs at 6 and 24 h were 174 and 191, respectively. As compared to upregulated genes, larger numbers of genes were downregulated. Stage-specific response to the GA3 application was observed as evident from the unique set of DEGs at each stage and only a few common genes among three stages. Among the DEGs, 67 were transcription factors. Functional categorization and enrichment analysis revealed that several transcripts involved in sucrose and hexose metabolism, hormone and secondary metabolism, and abiotic and biotic stimuli were enriched in response to application of GA3. A high correlation was recorded for real-time PCR and transcriptome data for selected DEGs, thus indicating the robustness of transcriptome data obtained in this study for understanding the GA3 response at different stages of berry development in grape. Chromosomal localization of DEGs and identification of polymorphic microsatellite markers in selected genes have potential for their use in breeding for varieties with improved bunch architecture.
Keywords: Bunch architecture; GA3 response; Microsatellite markers; RNA seq; Transcription factors; Vitis vinifera

Global study of MFS superfamily transporters in arabidopsis and grapes reveals their functional diversity in plants - Patil, Sucheta S.; Prashant, Ramya; Kadoo, Narendra Y.; Upadhyay, Anuradha; Gupta, Vidya S. (Plant Gene, 2019)
The Major Facilitator Superfamily (MFS) is the largest superfamily of secondary transporters present in all organisms, from prokaryotes to higher eukaryotes, that facilitates transport of diverse molecules like sugars, vitamins, amino-acids, hormones, etc. across cell membranes. The superfamily was further expanded to MFS Superfamily (MFSS) to integrate MFS with nine more families. The present study revealed their land plant specific diversity through identification across six species from unicellular alga to higher flowering plants. We identified 71, 131, 254, 260, 213 and 203 MFSS transporters in Chlamydomonas reinhardtii, Physcomitrella patens, Selaginella moellendorffii, Oryza sativa (var. Japonica), Arabidopsis thaliana and Vitis vinifera, respectively and classified them into MFSS families and subfamilies based on their transporter classification identifiers (TCIDs). Detailed analysis of 20 land plant specific subfamilies was conducted in A. thaliana and V. vinifera. Phylogenetic and gene duplication studies revealed the expansion of sugar porter and proton dependent oligopeptide transporter families in Arabidopsis and grape. The subcellular localization of the majority of the transporters was predicted to be in the plasma membrane. Furthermore, the microarray expression analysis of MFSS transporters from Arabidopsis and grapes revealed their multi-tissue-specificity and differential regulation under biotic and abiotic stress conditions. Studies of the transmembrane topology highlighted the presence of central cytoplasmic loop along with family specific topological variations that were evident from phylogenetic analysis. Overall, this study adds to the knowledge of functional and structural diversity and evolution of MFSS transporters in plants and opens the scope for detailed physiological and functional studies on these proteins.

Integrative omics analysis in Pandanus odorifer (Forssk.) Kuntze reveals the role of Asparagine synthetase in salinity tolerance - Rashmi, Deo; Barvkar, Vitthal T.; Nadaf, Altafhusain; Mundhe, Swapnil; Kadoo, Narendra Y. (Scientific Reports, 2019)
Pandanus odorifer (Forssk) Kuntze grows naturally along the coastal regions and withstands salt-sprays as well as strong winds. A combination of omics approaches and enzyme activity studies was employed to comprehend the mechanistic basis of high salinity tolerance in P. odorifer. The young seedlings of P. odorifer were exposed to 1 M salt stress for up to three weeks and analyzed using RNAsequencing (RNAseq) and LC-MS. Integrative omics analysis revealed high expression of the Asparagine synthetase (AS) (EC 6.3.5.4) (8.95 fold) and remarkable levels of Asparagine (Asn) (28.5 fold). This indicated that salt stress promoted Asn accumulation in P. odorifer. To understand this further, the Asn biosynthesis pathway was traced out in P. odorifer. It was noticed that seven genes involved in Asn bisynthetic pathway namely glutamine synthetase (GS) (EC 6.3.1.2) glutamate synthase (GOGAT) (EC 1.4.1.14), aspartate kinase (EC 2.7.2.4), pyruvate kinase (EC 2.7.1.40), aspartate aminotransferase (AspAT) (EC 2.6.1.1), phosphoenolpyruvate carboxylase (PEPC) (EC 4.1.1.31) and AS were up-regulated under salt stress. AS transcripts were most abundant thereby showed its highest activity and thus were generating maximal Asn under salt stress. Also, an up-regulated Na+/H+ antiporter (NHX1) facilitated compartmentalization of Na+ into vacuoles, suggesting P. odorifer as salt accumulator species.

Transcriptomics analysis of propiconazole-treated Cochliobolus sativus reveals new putative azole targets in the plant pathogen - Somani, Deepika; Adhav, Ragini; Prashant, Ramya; Kadoo, Narendra Y. (Functional & Integrative Genomics, 2019)
Cochliobolus sativus (anamorph: Bipolaris sorokiniana) is a filamentous fungus from the class Dothideomycetes. It is a pathogen of cereals including wheat and barley, and causes foliar spot blotch, root rot, black point on grains, head blight, leaf blight, and seedling blight diseases. Annual yields of these economically important cereals are severely reduced due to this pathogen attack. Evolution of fungicide resistant pathogen strains, availability of a limited number of potent antifungal compounds, and their efficacy are the acute issues in field management of phytopathogenic fungi. Propiconazole is a widely used azole fungicide to control the disease in fields. The known targets of azoles are the demethylase enzymes involved in ergosterol biosynthesis. Nonetheless, azoles have multiple modes of action, some of which have not been explored yet. Identifying the off-target effects of fungicides by dissecting gene expression profiles in response to them can provide insights into their modes of action and possible mechanisms of fungicide resistance. Moreover it can also reveal additional targets for development of new fungicides. Hence, we analyzed the global gene expression profile of C. sativus on exposure to sub-lethal doses of propiconazole in a time series. The gene expression patterns were confirmed using quantitative reverse transcriptase PCR (qRT-PCR). This study revealed overexpression of target genes from the sterol biosynthesis pathway supporting the reported mode of resistance against azoles. In addition, some new potential targets have also been identified, which could be explored to develop new fungicides and plant protection strategies.
Keywords: Bipolaris sorokiniana; Cochliobolus sativus; Fungicide resistance; Propiconazole; RNA-seq; Transcriptomics analysis

Whole proteome analysis of GA(3) response at panicle stage in Grape (Vitis vinifera) CV. Thompson seedless - Maske, Smita; Upadhyay, Anuradha; Jogaiha, Satisha; Patil, Sucheta S.; Kadoo, Narendra Y.; Gupta, Vidya S. (Journal of Plant Growth Regulation, 2019)
Rachis elongation is a crucial process in producing good quality table grapes. In compact clustered grape variety like Thompson Seedless, treating the flower panicles with a mild dose of GA(3) results in loose clusters. We sprayed GA(3) on Thompson Seedless panicles immediately after emergence, and the samples were collected at 6 h and 24 h after application. Whole proteome analysis revealed significant differential expression of 530 proteins of the total 1288 expressed proteins at two time-points. GO term enrichment analysis revealed enrichment of GO terms related to translation, biosynthetic processes, and photosynthesis in GA(3)-treated samples. As the process of rachis elongation requires enhanced carbon metabolism and accumulation of sugars through the expansion of phloem area, we attribute this to the overexpression of several proteins involved in these processes. Significantly highly expressed proteins also belonged to biological processes like the generation of precursor metabolites, cellular protein metabolic processes, response to abiotic stimulus, and protein metabolic processes. This study might be the first of its kind in deciphering the contribution of a different group of proteins during rachis elongation as an early response to GA(3) application in seedless grapes. These results provide quality information on various physiological and biochemical changes occurring during early stages of rachis elongation.
Keywords: Bunch architecture; Gibberellic acid; Proteome; Rachis elongation; Vitis vinifera

Insights of Bipolaris sorokinianasecretome-anin silicoapproach - Pathak, Gauri M.; Gurjar, Gayatri S.; Kadoo, Narendra Y. (Biologia, 2020)
The plant pathogen,Bipolaris sorokiniana(teleomorph:Cochliobolus sativus), is of global concern as it attacks many economically important cereals and grasses. During the infection process, phytopathogenic fungi are known to secrete a variety of proteins collectively known as the secretome, analyzing which can help in deciphering the mechanism of fungal pathogenesis. In this study, we performedin silicosecretome analysis ofC. sativusstrain ND90Pr using established secretome prediction pipeline involving software tools such as SignalP, TargetP, TMHMM, big-PI Fungal Predictor, ProtComp, and WoLF PSORT. Using these software and other prediction criteria, we identified 196 probable secretory proteins from theB. sorokinianaproteome. Characterization of the predicted secretome revealed proteins that may have probable functions in degradation of the plant cell wall, lipids, proteins, and nucleic acids, as well as in pathogenesis and metabolism. Further, the PHI-base analysis identified 38 proteins having a possible role in pathogenicity and virulence. This study helped to predict the composition of the secretome ofB. sorokinianaand extrapolate its role in plant infection and pathogen survival. It may provide clues for developing new control strategies targeting the vital fungal secretory proteins.
Keywords: Cochliobolus sativus; pathogenesis; Phytopathogenic fungi; Secretory proteins; Virulence

Gibberellic acid induces unique molecular responses in `thompson seedless' grapes as revealed by non-targeted metabolomics - Jadhav, Uma; Mundhe, Swapnil; Kumar, Yashwant; Jogaiah, Satisha; Upadhyay, Anuradha; Gupta, Vidya S.; Kadoo, Narendra Y. (Journal of Plant Growth Regulation, 2021)
Compact clusters and small berry size are the major problems associated with the commercialization of table grapes. The application of gibberellic acid 3 (GA(3)) has been a long-followed practice to overcome these issues. To analyze the molecular response of `Thompson Seedless' grapes to GA(3) treatment, we investigated the metabolomes of its rachises, clusters, and berries, 6 h and 24 h after the treatment. Metabolite profiling using non-targeted metabolomics approach revealed several metabolites, including arginine, proline, tyrosine, kaempferol, resveratrol, catechin, and so on as possible biomarkers of GA(3) treatment in grapes. GA(3) treatment greatly impacted the alanine, aspartate, and glutamate metabolism pathways, and the GA(3)-mediated alterations in the levels of certain plant growth regulators and primary metabolites were in accordance with important growth and developmental processes in grapes. This study highlights the effect of GA(3) on the profiles of certain polyphenols impacting the flavone and flavonol biosynthesis pathways and hence the nutritional aspect of grapes. The results of this study would be useful to develop self-elongating varieties simplifying the grape cultivation.
Keywords: Biosynthetic pathways; GA(3) response; GA(3) signaling; Sultana grapes; Untargeted metabolomics

Gibberellic acid induces unique molecular responses in ‘thompson seedless’ grapes as revealed by non-targeted metabolomics - Jadhav, Uma; Mundhe, Swapnil; Kumar, Yashwant; Jogaiah, Satisha; Upadhyay, Anuradha; Gupta, Vidya S.; Kadoo, Narendra Y. (Journal of Plant Growth Regulation, 2021)
Compact clusters and small berry size are the major problems associated with the commercialization of table grapes. The application of gibberellic acid 3 (GA3) has been a long-followed practice to overcome these issues. To analyze the molecular response of ‘Thompson Seedless’ grapes to GA3 treatment, we investigated the metabolomes of its rachises, clusters, and berries, 6 h and 24 h after the treatment. Metabolite profiling using non-targeted metabolomics approach revealed several metabolites, including arginine, proline, tyrosine, kaempferol, resveratrol, catechin, and so on as possible biomarkers of GA3 treatment in grapes. GA3 treatment greatly impacted the alanine, aspartate, and glutamate metabolism pathways, and the GA3-mediated alterations in the levels of certain plant growth regulators and primary metabolites were in accordance with important growth and developmental processes in grapes. This study highlights the effect of GA3 on the profiles of certain polyphenols impacting the flavone and flavonol biosynthesis pathways and hence the nutritional aspect of grapes. The results of this study would be useful to develop self-elongating varieties simplifying the grape cultivation.

Diversity assessment of Gloriosa superba accessions from Western Ghats of India based on morphological traits, ISSR markers and metabolite content - Mahajan, Yogesh A.; Shinde, Balkrishna A.; Mulani, Fayaj A.; Gade, Akshay B.; Kasodekar, Amol K.; Thulasiram, H. V.; Kadoo, Narendra Y.; Nikam, Tukaram D. (Journal of Applied Research on Medicinal and Aromatic Plants, 2022)
Gloriosa superba L. (glory lily) is a medicinally and horticulturally important plant used as a commercial source of the alkaloid colchicine. The Western Ghats in India is mostly unexplored for the morphological, genetic, and metabolite diversity of the species. In the current study, three methodologies were employed to assess the diversity among 50 established accessions of G. superba collected from several locations in the Western Ghats. The morphological analysis revealed that, among the studied traits, seed yield per vine and dry seed weight per 100 seeds for the established accessions were the most diverse traits. The former exhibited a significantly positive correlation with four vegetative and five yield traits. The first three principal components showed nine traits contributing to the variation. Intra-specific molecular variation based on inter simple sequence repeat markers distributed the accessions in three clusters with high polymorphism and low genetic diversity indices. Liquid chromatography high-resolution mass spectrometry analysis revealed significant variation among the screened accessions for colchicine content in tuber and seed tissue. Interestingly, an unexplored tissue, pod shell, was found to contain significantly high colchicine, which could be explored for commercial colchicine extraction. The morphogenetic and metabolite variation revealed by the study would be useful to develop elite varieties to expand the cultivation of glory lily across the country, fulfilling the increasing demand for colchicine and providing remunerative income to the farmers.
Keywords: Colchicine; Genetic diversity; Gloriosa superba; Metabolite diversity; Morphological diversity; Western Ghats

Role of ions and their transporters in combating salt stress in Pandanus odorifer (Forssk.) Kuntze - Rashmi, Deo; Ansari, Waquar A.; Kadoo, Narendra Y.; Barvkar, Vitthal T.; Deshmukh, Rupesh; Nadaf, Altafhusain B. (Acta Physiologiae Plantarum, 2023)
Soil salinity is a major environmental constraint causing huge losses in crop production. Pandanus odorifer (Forssk.) Kuntze is an aromatic monocot plant species belonging to the family Pandanaceae, which grows naturally on the saline soils along the coasts of Asia, Southeast Asia, and Polynesia. The plants are dioecious and highly fertile, and the consistent saline sprays, strong winds, and severe soil salinity hardly affect their growth and fertility. Hence, understanding the mechanism of high salinity tolerance in P. odorifer could provide major advances in overcoming salinity stress in crop plants. In the present study, we analyzed control (0 M NaCl) and treated (1 M NaCl treatment for 3 weeks) plants of P. odorifer to understand the role of ion distribution, ion transport, and related mechanisms under salt stress. Using a combination of ionomics and transcriptomics approaches, we identified the molecular mechanisms contributing to the high salinity stress in P. odorifer. Under NaCl stress, there was a significant increase in Na, Cl, and other ions in leaves, while the concentrations of Si, Fe, Ni, and Ti decreased. Similarly, in roots, the levels of Na, Mg, Cd, and Cr were significantly high, while the levels of other ions decreased. Most of the genes related to ion transport and homeostasis, such as NHX1, CLC-C, SOS1, HAK, and ABC transporters, were upregulated in 1 M NaCl stress conditions. This study revealed that vacuolar sequestration of Na+ and the distribution of ions in the roots and shoots play significant roles in the salt-stress tolerance mechanism of P. odorifer.
Keywords: Ion transport; Ionomics; Pandanus; Salinity tolerance; Transcriptomics; Vacuolar sequestration

Seasonal dynamics and tree foliar habit drive the rhizobacterial diversity in congeneric Ficus species from Northern Western Ghats, India - Salunkhe, Vaishnavi H.; Kunte, Pooja S.; Paul, Dhiraj; Kasodekar, Amol K.; Kadoo, Narendra Y. (Rhizosphere, 2023)
Tree species, annual climatic cycle, and geochemical properties influence the tree rhizospheric microbiome. However, its understanding in the moist deciduous forest of Northern Western Ghats (NWG), India, is limited. Moreover, the effects of foliar habits of trees and seasonal variations on rhizobacterial communities across congeneric tree species are unexplored. Hence, we employed high throughput 16 S rRNA gene sequencing to examine the effects of foliar habits of congeneric tree species and seasonal influences on the rhizobacterial community. For this study, rhizospheric soil from Ficus arnottiana (deciduous) and Ficus talboti (evergreen) trees from NWG, India, was collected during three seasons (summer, monsoon, and winter) and subjected to high throughput sequencing. A total of 3031 amplicon sequence variants (ASV) were observed, of which 1257 and 1181 ASV were unique to F. arnottiana and F. talboti, respectively, and 593 ASV were common to both species. The phyla Actinobacteria, Proteobacteria, Acidobacteria, and Chloroflexi were ubiquitous and contributed >90% to the rhizobacterial community. Some bacterial phyla were exclusively associated with either of the tree species and seasons. Different bacterial phyla performed similar functions in different seasons, indicating their functional redundancy and emphasizing their resilience and adaptability across seasons. It was observed that seasonal dynamics mainly drove the rhizobacterial diversity; however, it was also influenced by the foliar habits of the trees and geochemical properties. The study enhances the understanding of congeneric tree microbiomes and offers valuable insights into their potential applications through microbiome engineering.
Keywords: Amplicon variants; Bacterial diversity; Ficus arnottiana; Ficus talboti; Rhizosphere

Unlocking the genetic and biotechnological potential of Gloriosa superba to enhance its alkaloid production - Mahajan, Yogesh A.; Shinde, Balkrishna A.; Shirke, Harshad A.; Gandra, Jawahar; Suravajhala, Prashanth; Kishor, P. B. Kavi; Kadoo, Narendra Y.; Nikam, Tukaram D. (Industrial Crops and Products, 2024)
Gloriosa superba is a medicinally important plant that produces the pharmaceutically precious colchicine molecule. Colchicine is being used for treating gout, for enhancing the production of interleukin-8 (inhibits human pancreatic cancer) and many other human ailments. Since its seeds and rhizomes (tuberous roots) are the chief sources of colchicine, pharmaceutical industries exploit the natural sources, thus demolishing its habitat. Chemo- and genetic diversity among the G. superba populations exist, but has not been exploited profitably. Scope exists for generating mutants using the chemical mutagens and also via breeding methods to generate superior varieties for commercial cultivation. Innovative methods for breaking seed dormancy and superior colchicine extraction, besides biotechnological interventions are imperative to save the biodiversity and to produce colchicine on a large scale. Biorhizomes produced in vitro hold great promise for biomanufacturing colchicine in bioreactors commercially. Since the biosynthetic pathway of colchicine is now known, isolation of the pathway genes and their heterologous overexpression or the application of synthetic biology methods needs to be explored in future for industrial manufacturing of colchicine. Advances made in the recent past in these fields of colchicine production from G. superba are critically evaluated in this review.
Keywords: Biosynthetic pathway; Colchicine; Genetic diversity; Glory lily; Metabolite elicitation; Omics approaches

Harnessing microRNAs and their targets for salt stress tolerance in Pandanus odorifer - Rashmi, Deo; Barvkar, Vitthal T.; Nadaf, Altafhusain B.; Kadoo, Narendra Y. (Journal of Plant Biochemistry and Biotechnology, 2025)
Salinity poses a formidable challenge to agriculture, detrimentally impacting plant growth and the yield of several crops globally. Pandanus odorifer (Forssk.) Kuntze is a highly salt-stress resilient plant that grows naturally along the coastal regions of Asia, Southeast Asia, and Polynesia. It is frequently found as a frontier species along the sandy shores receiving constant salt sprays. MicroRNAs (miRNAs) play essential regulatory roles in growth, development, and combating various biotic and abiotic stresses. Thus, characterizing miRNAs and their targets is critical to understanding their roles in salt stress tolerance. Through a rigorous analysis based on homology, secondary structure and signatures of other miRNA genes, we identified 52 conserved nonredundant miRNAs from the P. odorifer transcriptome data. These miRNAs were diverse and belonged to 23 miRNA phylogenetic families. Several miRNAs, including pod-MIR156a, pod-MIR164d, and pod-MIR535d, demonstrated distinct expression patterns in response to salt stress. Their target genes exhibited opposing expression trends, corroborating the intricate miRNA-target relationship. Delving deeper into their influence, we discovered that these miRNAs mainly targeted transcription factors that are known for their pivotal roles in stress responses. We also detected four miRNA-star (miRNA*) sequences (the complementary strands of functional mature miRNAs), which supports the authenticity of the identified miRNAs. This study unveils the intricate regulatory mechanism through which miRNAs may reinforce salt stress tolerance in P. odorifer, providing a promising avenue for enhancing crop resilience to various stresses through miRNA-based strategies.
Keywords: Abiotic stress; microRNA; miRNA targets; Salinity tolerance; salt stress; Transcription factors

Integrative multi-omics and computer-aided biofungicide design approach to combat fusarium wilt of chickpea - Sahoo, Rosaleen; Kadoo, Narendra Y. (Planta, 2025)
Main conclusionIntegrating multi-omics and computer-aided drug discovery approaches can overcome the limitations of traditional methods and help develop highly effective, specific, and environmentally safe biofungicides to control crop diseases.AbstractChickpea is a valuable legume crop in terms of nutrition, food security, economic sustainability, and environmental benefits. Fusarium wilt caused by the soil-borne fungus Fusarium oxysporum f.sp. ciceri is one of the most important diseases affecting chickpea. Several disease management methods, including crop rotation, soil fumigation with chemical fungicides, soil solarization, etc., are practiced to manage the disease. However, these methods have various limitations and cannot completely control the disease. Moreover, chemical fungicides indiscriminately kill even the beneficial soil microbes, pollute groundwater, and enter the food chain. Hence, modern approaches emphasizing innovative strategies and technologies need to be explored to manage the disease effectively. In this review, we propose integrating multi-omics (genomics, proteomics, metabolomics, etc.) and computer-aided drug discovery (CADD) approaches to develop biofungicides targeting vital pathogen proteins. Multi-omics approaches can delve deeper into the plant-pathogen interaction and reveal essential pathogen genes or proteins. These proteins could be targeted using CADD to identify phytochemical-based potential biofungicides, either using structure- or ligand-based drug design approaches. The potential biofungicides can be subjected to the prediction of carcinogenicity, hepatotoxicity, mutagenicity, etc., to identify biofungicides that are safe to use and are highly specific to the target pathogen. In vivo and in vitro validation studies can be followed to establish the efficacy and safety of the identified biofungicides for their practical application. This integrated approach can reduce the time and cost compared to the traditional methods and accelerate the discovery of highly effective biofungicides to protect crops from various diseases.
Keywords: CADD; docking; Fungal diseases; MD Simulation; Protein structure prediction; Transcriptomics

Transcriptome analyses reveal TaWRKY41 as a potential candidate governing spot blotch resistance in wheat - Dayama, Bhakti R.; Mahadik, Varsha A.; Somani, Deepika; Shinde, Balkrishna A.; Kondhare, Kirtikumar R.; Karthikeyan, Muthukumarasamy; Kadoo, Narendra Y. (Physiology and Molecular Biology of Plants, 2025)
Spot blotch disease caused by Bipolaris sorokiniana poses a significant threat to wheat production. Cultivation of disease-resistant wheat genotypes appears to be the most practical approach to mitigate the impact of this devastating disease. However, the molecular responses of wheat plants during spot blotch disease progression remain poorly understood. This study employed RNA-sequencing to unravel the spatiotemporal molecular events underlying the resistance mechanism in the spot blotch susceptible and resistant wheat genotypes. This study further provides a comprehensive overview of differentially expressed transcripts through functional analysis and transcription factor identification, elucidating the biological mechanisms governing wheat-B. sorokiniana interaction. In the resistant genotype, the expression of one of the key transcription factors, TaWRKY41, was significantly induced upon pathogen inoculation. Computational studies, electrophoretic-mobility shift assay, and yeast one-hybrid assay confirmed the interaction of the recombinant TaWRKY41 protein with W-box elements present in the promoters of plant defense-related genes. Furthermore, co-expression network analyses identified downstream genes positively correlated with TaWRKY41, providing insights into their probable involvement in the defense response. Overall, our investigation suggests that TaWRKY41 contributes to spot blotch resistance in wheat. This knowledge can help develop new disease-resistant wheat varieties.
Keywords: Plant defense; plant-pathogen interaction; TaWRKY41; Transcription factors; Transcriptomics